2008
DOI: 10.1007/bf03086137
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the flow velocity-pressure gradient relation in the assessment of stenoses: an in vitro study

Abstract: Objectives. The flow velocity-pressure gradient (v-dp) relation is clinically used to assess coronary stenoses. This in vitro study aimed to investigate the ability to determine the impact of each individual stenosis in the setting of two consecutive stenoses, the effect of variable stenosis reference diameters and the impact of one or two wires in a stenosis, on the v-dp relation. Methods. The model consisted of a reservoir and different sized tubes and stenoses. Pressure gradient and flow velocity were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…An alternative means for invasive flow measurements is presented by the calculation of models in which blood flow can be virtually simulated, a method that is called computational fluid dynamics (CFD). In fact, several in vitro studies [6,10,16,17,18] have shown that CFD allows reliable physiologic blood flow simulation and measurements of WSS, wall pressure, and mass flow. A detailed hemodynamic evaluation of disturbed flow in the post stenotic region may give additional insight of the progression of atherosclerosis and may have useful clinical value, such as early detection of a highly stenosed artery segment, prediction of future disease progression, and treatment planning 2.1 Artery reconstruction A Somatom Sensation 64 Scanner (Siemens Medical Systems, Erlangen, Germany) was used in non-enhanced spiral scan technique with a slice thickness of 0.75 mm, a table feed of 1 mm/s, and an increment of 2 mm (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative means for invasive flow measurements is presented by the calculation of models in which blood flow can be virtually simulated, a method that is called computational fluid dynamics (CFD). In fact, several in vitro studies [6,10,16,17,18] have shown that CFD allows reliable physiologic blood flow simulation and measurements of WSS, wall pressure, and mass flow. A detailed hemodynamic evaluation of disturbed flow in the post stenotic region may give additional insight of the progression of atherosclerosis and may have useful clinical value, such as early detection of a highly stenosed artery segment, prediction of future disease progression, and treatment planning 2.1 Artery reconstruction A Somatom Sensation 64 Scanner (Siemens Medical Systems, Erlangen, Germany) was used in non-enhanced spiral scan technique with a slice thickness of 0.75 mm, a table feed of 1 mm/s, and an increment of 2 mm (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This recirculation zone creates the secondary stenosis. Marques and Westerhof [6], Kangl et al [7] have carried out experimental studies related to flow dynamics in constricted vessels. They suggested that the flow energy loss due to the presence of the stenoses, which is directly related to the pressure drops across them, increases with the number of stenoses and is not strongly dependent on the spacing between them.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular dysfunction is generally considered a key initial event in the atherosclerotic process which is a systemic disorder local manifestation. Functional changes in arteries precede the development of structural changes and also reverse more quickly in response to therapies [ 44 ]. Fingertip digital thermal monitoring (DTM) of vascular reactivity is a new non-invasive, operator-independent approach based on changes in fingertip temperature during and after arm cuff occlusion.…”
mentioning
confidence: 99%
“…The advent of prospectively gated acquisition techniques for 64-slice CT angiography has allowed a significant reduction in dose exposure. Consequently, a combined approach of CT coronary angiography and myocardial perfusion imaging with CT angiography might potentially become feasible at a total radiation dose of less than 10 mSv, particularly for the assessment of patients with established CAD, who are likely to have diffuse calcification [ 40 47 ].…”
mentioning
confidence: 99%